Chemotherapy decisions and patient experience with the recurrence score assay for early‐stage breast cancer. Issue 1 (24th October 2016) - Friese, Christopher R.; Li, Yun; Bondarenko, Irina; Hofer, Timothy P.; Ward, Kevin C.; Hamilton, Ann S.; Deapen, Dennis; Kurian, Allison W.; Katz, Steven J.
Abstract : BACKGROUND: The 21‐gene recurrence score (RS) assay stratifies early‐stage, estrogen receptor–positive breast cancer by recurrence risk. Few studies have examined the ways in which physicians use the RS to recommend adjuvant systemic chemotherapy or patients' experiences with testing and decision making. METHODS: This study surveyed 3880 women treated for breast cancer in 2013‐2014; they were identified from the Los Angeles County and Georgia Surveillance, Epidemiology, and End Results registries (response rate, 71%). Women reported chemotherapy recommendations, the receipt of chemotherapy, testing experiences, and decision satisfaction. Registries linked the tumor data, RS, and surveys. Regression models examined factors associated with chemotherapy recommendations and receipt by the RS and subgroups. RESULTS: There were 1527 patients with stage I/II, estrogen receptor/progesterone receptor–positive, human epidermal growth factor 2–negative disease: 778 received an RS (62.6% of patients with node‐negative, favorable disease, 24.3% of patients with node‐negative, unfavorable disease, and 13.0% of patients with node‐positive disease; P < .001). Overall, 47.2% of the patients received a recommendation against chemotherapy, and 40.5% received a recommendation for it. RS results correlated with recommendations: nearly all patients with high scores (31‐100) received a chemotherapy recommendation (86.9%‐96.5% across clinical subgroups), whereas the majority of the patients with low‐risk results (0‐18) received a recommendation against it (65.9%‐78.2% across subgroups). Most patients with high RSs received chemotherapy (87.0%, 91.1%, and 100% across subgroups), whereas few patients with low scores received it (2.9%, 9.5%, and 26.6% across subgroups). There were no substantial racial/ethnic differences in testing or treatment. Women were largely satisfied with the RS and chemotherapy decisions. CONCLUSIONS: Oncologists use the RS to personalize treatment, even for those with node‐positive disease. High satisfaction and an absence of disparities in testing and treatment suggest that precision‐medicine advances have improved systemic breast cancer treatment. Cancer 2017;43–51. © 2016 American Cancer Society. Abstract : In a population‐based sample of women diagnosed with early‐stage breast cancer, the majority of women, including a third of women with lymph node–positive disease, received 21‐gene recurrence score testing. The test results correlated with guideline‐recommended treatment in most cases, and patient satisfaction was high.